Sickness presenteeism of German teachers: prevalence and influencing factors. Issue 2 (17th February 2017) - Dudenhöffer, Sarah; Claus, Matthias; Schöne, Klaus; Letzel, Stephan; Rose, Dirk-Matthias
Abstract: The aim of the present study was to investigate teachers' sickness presenteeism (SP). We examined the prevalence of SP in a sample of teachers as well as work-related and health-related influencing factors of teachers' SP. We used a cross-sectional study design. Teachers working at different types of schools in Rhineland-Palatinate (Germany) participated in an online survey. We used Pearson's Chi-squared test (in case of categorical variables) or Mann–Whitney- U -test (in case of continuous variables) to test for differences between SP and sociodemographic/work-related/health-related factors. Factors influencing SP were identified using multivariable logistic regression analyses. Nine hundred and twenty-four teachers working at 42 different schools completed the questionnaire (response proportion: 50.1%). The prevalence of SP in our study was 57.1%. The multivariable logistic regression analyses showed less support by supervisors (aOR: 1.77; 95-CI: 1.21–2.60), inappropriate administration efforts (aOR: 1.56; 95-CI: 1.16–2.11), and inappropriate recognition of performance (aOR: 1.44; 95-CI: 1.04–198) as well as exhaustion/fatigue (aOR: 2.29; 95-CI: 1.71–3.08) as main predictors of teachers' SP. SP is widespread among teachers. As SP is associated with impairment of psychological and physical health in the long run, it is important to implement measures to reduce SP. A climate of support and cooperation as well as assistance for ill teachers to deal with work missed due to absence might be useful strategies.